Life‐threatening pontine hemorrhage secondary to HELLP syndrome - Sajjad Ali; Sara Anjum Fazal; Syed Abdullah Monawwer; Mahfuza Anan (Clinical Case Reports, 2023)
Key Clinical Message HELLP syndrome is a severe form of pre‐eclampsia that typically develops prior to delivery but can sometimes happen postpartum. The classic triad of HELLP syndrome comprises of hemolysis, elevated liver enzyme levels, and low platelet counts. This condition is known to have a higher incidence of fatal neurological complications, such as pontine hemorrhage, when compared to a typical pre‐eclampsia.